Diagnosing Nonlocal Vertical Acceleration in Moist Convection Using a Large‐Eddy Simulation - Fu‐Sheng Kao; Yi‐Hung Kuo; Chien‐Ming Wu (Journal of Advances in Modeling Earth Systems)
Abstract The anelastic theory of effective buoyancy has been generalized to include effects of momentum flux convergence, and has suggested that the dynamics—mediated by the nonlocal perturbation pressure—tends to average over forcing details, yielding vertical acceleration robust to small‐scale variations of the flow. Here we aim to substantiate this theoretical assertion through examining a large‐eddy simulation (LES) with a 100‐m horizontal grid spacing. Specifically, instances of convection in the LES are identified. For these, the buoyancy and dynamic contributions to the vertical momentum tendency are separately diagnosed, and their sensitivity resulting from averaging over sub‐cloud‐scale features quantified. In the absence of a background shear or vorticity, both buoyancy and vertical momentum flux convergence are the leading effect in the vertical acceleration while the influence of the horizontal momentum flux convergence on the vertical motion appears to be substantially weaker. For deep‐convective cases, these contributions at the cloud scale (∼8 km) exhibit a robustness, as measured in a root‐mean‐square sense, to horizontally smoothing out turbulent features of scales ≲3 km. As expected, such scales depend on the size of the convective element of interest, while dynamic contributions tend to be more susceptible to horizontal smoothing than does the buoyancy contribution. We thus argue that including the anelastic nonlocal dynamics can help capture the evolution of convective‐cloud‐scale flows without fully resolving the finer‐scale turbulent features embedded in the flow. Results here lend support to simplifying the subgrid‐scale representation of moist convection for global climate models and storm‐resolving simulations.